O ensino do lugar e o lugar do ensino: o conceito de lugar geográfico como dimensão de uma educação emancipadora no ciclo II do ensino fundamenta - Azevedo, Mariângela Oliveira de (2016)
Human sciences in general, and Geography, in particular, have characteristics that can contribute to the criticality of the subjects from the training concepts, indispensable to understanding the world and its transformation. The concept of place in Geography, may enable broad critical reflections of the world, therefore, because this globalized, conflicts and socio-spatial relations are not restricted the particularities of one or the other place. The place is articulated to the global total, characterized as a contradictory space of hegemonic domination and critical resistance and humanizing. From the foregoing, the present study sought to problematize the teaching of Geography, the relationship between the concept of place and possibility of an education that is proposed emancipating in the Second Cycle of the Fundamental Education. We tried to articulate the discussions of teaching of Geography and the concept of place, the visions of the world, the human being and the concept of Geography and its history. The method of analysis outlined in the historical dialectical materialism by considering the school education as a human and social activity. Still, we tried to show that Geography, since elementary school can be useful for reading and understanding the world in its complexity and that the concept of place is can configured itself as revealing the reality of the new demands of economic globalization. Objectifying praxis of the research, we conducted investigations and analysis of how the content of Geography that deals with the concept of place have been covered in the Second Cycle of Elementary School and what kind of knowledge can be created from the practices of pedagogical that are used for such practices.The reflections arising from the research, at the end , based us in the preparation of a didactic proposal approach to the concept of place, having the neighborhood as a content.